Pengembangan Media Physics Game Learning pada Konsep Perubahan Wujud Zat - Rino, Aji Pancer Agung; Ruhiyat, Yayat; Wibowo, Firmanul Catur (UPEJ Unnes Physics Education Journal, 2019)
This research aims to obtain the characteristics of media physics game learning on the concept of substance change and to determine the feasibility of media physics game learning developed in the concept of substance change. The research method used consisted of five steps namely needs analysis, learning design, media development, product evaluation and product production. with research and development research design. The results show that media physics learning games on each display are equipped with navigation buttons, particle images and instructions. The average score of media expert validation score is 96% with very feasible category, the average score for material expert validation is 98% with very feasible categories and the results of the average student response are 86% with very good categories. Thus it can be concluded that the physics characteristics of learning games is a simulation in the form of a simple game that displays the process of changing matter visually and microscopically. Media physics game learning is worthy of being an alternative medium in learning in the classroom